Balancing acts: the dual faces of fentanyl in medicine and public health - Khatoon, Hena; Mohd Faudzi, Siti Munirah (Elsevier B.V., 2024)
Fentanyl is a potent synthetic opioid widely used in medicine for its effective analgesic properties, particularly in surgical procedures and in the treatment of severe, chronic pain. In recent decades, however, there has been a worrying increase in the illicit use of fentanyl, particularly in North America. This rise in illicit use is concerning because fentanyl is associated with polydrug abuse, which adds layers of complexity and dangerous. This review provides a comprehensive examination of fentanyl, focusing on its synthesis and medical use. It also discusses the significance of the piperidine ring in medicinal chemistry as well as the critical role of fentanyl in pain management and anesthesia. Furthermore, it addresses the challenges associated with the abuse potential of fentanyl and the resulting public health concerns. The study aims to strike a balance between the clinical benefits and risks of fentanyl by advocating for innovative uses while addressing public health issues. It examines the chemistry, pharmacokinetics and pharmacodynamics of fentanyl and highlights the importance of personalized medicine in the administration of opioids. The review underscores the necessity of continuous research and adaptation in both clinical use and public health strategies.